VirtueAll: Television Talkshow Program Based on Virtual Live Streaming - Nyoman Lia Susanthi; Ketut Hery Budiyana; Igor de Almaida Amanajas; I Wayan Suardana (Institut Seni Indonesia Denpasar, 2023)
The Covid-19 pandemic has changed the order of life in various sectors, including education. In 2020 online learning was applied to the Advanced Tv Production class, Film and TV Production Study Program, Faculty of Fine Arts and Design, ISI Denpasar. Changes in the behavior of classroom practice in producing tv programs have shifted virtually. Even though students in groups created a weekly talk show program called “VirtueAll” they held it face-to-face. The purpose of this study is to recognize how the production process of the ViertueAll program based on virtual live streaming. In this study, the author used a qualitative descriptive research design. Descriptive research is a study to collect information about the transformation of the form of television production into virtual. The results showed that: The virtual live streaming production process used two stages, namely pre-production, preparation of the production design for the VirtueAll tv program, and agenda setting. The production stage is to change the production design into audiovisual. In the production of virtual live streaming using several platforms, including Google Meet, Zoom and OBS (Open Broadcaster Software). Google Meet facilities as a virtual master control room (MCR) and zoom as a virtual studio. The positive impact of this research is beneficial for the community to provide knowledge to become content creators with minimalist and adaptive tools to the current pandemic conditions. The negative impact is less appreciative to interact as a team work in production team and highly dependent on the readiness of technology including high specification computers and a good internet network.